Assessment of the Malls In Terms of Comfort Condition for Consumers - Tunçbilek, Hüseyin; Deniz, Gökmen (Proceedings of the international conference of contemporary affairs in architecture and urbanism-ICCAUA, 2020)
Malls which numbers are lately increasing has been a part of social and cultural way of life and host a lot of visitors. Malls are preferred excessively because it has same indoor climate condition all the year round. Target: In this study there will be an assessment through analyzing the physical comfort conditions of two malls in Turkey. Content: While assessing the malls in terms of comfort conditions, indoor temperature, air quality, lighting, aural comfort will be reviewed. Method: Going to the malls, observing the area one-to-one, making the fieldwork, benefiting from sweep literature. Conclusion: to assess the malls in terms of comfort conditions and offer a suggestion about malls that will be designed.